Dampak Kebijakan Ekonomi Internasional Terhadap Pertumbuhan Ekonomi Indonesia Sebagai Negara Berkembang - Rika Lailatul Fitri; Lailatul Fitria; Oky Mukhofifah; Zahwa Nabila Maharani; Fahmi Prayoga; Putri Catur Ayu Lestari (CV. ITTC INDONESIA, 2025)
Global economic policies play an important role in regulating economic interactions among countries, covering aspects such as trade, capital flows, foreign investment, and various forms of international cooperation. The purpose of this study is to understand how these policies influence Indonesia’s economic growth as a developing country. This research employs a qualitative approach and descriptive analysis by reviewing literature from various references, including books, scientific articles, and official documents related to economic policy. The findings indicate that economic openness can enhance productivity, expand market opportunities, encourage innovation, and attract foreign investment that contributes to economic growth. Theories of comparative advantage and modern growth theory also emphasize that participation in the global economy can provide benefits through production efficiency and the adoption of new technologies. On the other hand, there are potential risks such as increasing dependence on imports, pressures faced by MSMEs, income inequality, and vulnerability to global shocks when domestic economic readiness remains weak. Overall, the study shows that international economic policies yield better outcomes when supported by the strengthening of domestic industries, improved technological capacity, and social policies that maintain balance and equitable development.